CHARACTERIZATION OF FRUIT ON SEVERAL SALAK VARIETIES AND THEIR HYBRIDS - Hadiati, Sri; Budiyanti, T.; Soemargono, A.; Susiloadi, A. (AGRIVITA, Journal of Agricultural Science, 2012)
The objective of this study was to characterize salak of local varieties and their hybrids. The fruits characterized were taken from plants that were grown in October 2004. The results revealed that fruits Â³ 61 g were mostly produced by hybrids, in which one of their parents was Mwr or Ph. Fruits with flesh thickness Â³ 0.85 cm were mostly yielded from Sdp, Sdm, and hybrids where one of their parents was Sdp or Mwr. While fruits with edible portion Â³ 65.0% were mostly yielded from Sdp, Gp, and hybrids where their female parents were Mwr, Ph, and Sdp. Fruits with small seeds (â¤ 3.0 g) were observed on Gp, whilst those with big seeds (â¥ 7.0 g) were on Sdm, Sdm-Sj and Sdp-Sj. Hybrids from the female of Ph and Sdp mostly gave sweet taste (TSS â¥ 20Âº Brix). Mwr x Sdp crossing produced non-astringent fruits, while Ph x Java (K, M, Mj), Sdp x Sjg and some Sdp x Mwr crossing as well as Mwr produced astringent fruits. The four superior characters, namely fruit â¥ 61 g, flesh thickness Â³ 0.85 cm, edible portion â¥ 65%, and TSS â¥ 20Âº Brix were found in Mwr-Sp-8, Sdp-Sj-8, and Â Â Â Â Â Â Â Â Â Ph-M-7. Fruits produced by Mwr-Sp-8 were not astringent, while those produced by Sdp-Sj-8 and Ph-M-7 were astringent. These findings suggest that the selection of parent can play an important role in improving the varieties of salak. Keywords: salak, characterization, variety, hybrid, fruit